All Days 2007
DOI: 10.2118/110408-ms
|View full text |Cite
|
Sign up to set email alerts
|

Success of SAG Foam Processes in Heterogeneous Reservoirs

Abstract: fax 01-972-952-9435. AbstractIn principle, miscible gas injection can displace nearly all of the oil from the portions of a reservoir swept by gas. However, reservoir heterogeneity, low gas density and high gas mobility reduce sweep efficiency and drastically decrease recovery. Fortunately, the use of foam can reduce gas mobility and the effect of heterogeneity and therefore increase sweep efficiency. Based on the work of Shan and Rossen, an optimal design strategy is proposed here for surfactant-alternating-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
1
25
1
Order By: Relevance
“…In our current work, the surfactant concentration and dry-out effects are considered and some typical values are chosen, as shown in Table 1. Here, we chose 100 for fmmob, which is less than these employed by earlier researchers, such as 1000 (Rossen et al 2006), 3000 (Rossen and Shen 2007;Jamshidnezhad et al 2008a), or 5000 (Cheng et al 2000;Rossen and Renkema 2007;Kloet et al 2009), because we believe too strong foam used previously masked some details in the foam process, which is crucial for the novel foam. Meanwhile, it is also much less than the result of coreflood matching (Ma et al 2013) because the foam in 3D is much weaker than in 1D, which has been demonstrated by Li et al (2006).…”
Section: Reservoir Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…In our current work, the surfactant concentration and dry-out effects are considered and some typical values are chosen, as shown in Table 1. Here, we chose 100 for fmmob, which is less than these employed by earlier researchers, such as 1000 (Rossen et al 2006), 3000 (Rossen and Shen 2007;Jamshidnezhad et al 2008a), or 5000 (Cheng et al 2000;Rossen and Renkema 2007;Kloet et al 2009), because we believe too strong foam used previously masked some details in the foam process, which is crucial for the novel foam. Meanwhile, it is also much less than the result of coreflood matching (Ma et al 2013) because the foam in 3D is much weaker than in 1D, which has been demonstrated by Li et al (2006).…”
Section: Reservoir Modelmentioning
confidence: 99%
“…Meanwhile, it is also much less than the result of coreflood matching (Ma et al 2013) because the foam in 3D is much weaker than in 1D, which has been demonstrated by Li et al (2006). In simulations, we made fmsurf equal to the injected surfactant concentration (3.34 9 10 -5 , molar fraction) (Hanssen et al 1994;Rossen and Renkema 2007). A linear dependence between foam strength and surfactant concentration was chosen (epsurf = 1) (Rossen and Renkema 2007).…”
Section: Reservoir Modelmentioning
confidence: 99%
See 3 more Smart Citations